An alphacoronavirus polymerase structure reveals conserved replication factor functions - Anderson, Thomas K; Hoferle, Peter J; Chojnacki, Kennan J; Lee, Kenneth W; Coon, Joshua J; Kirchdoerfer, Robert N (Nucleic acids research, 2024)
Coronaviruses are a diverse subfamily of viruses containing pathogens of humans and animals. This subfamily of viruses replicates their RNA genomes using a core polymerase complex composed of viral non-structural proteins: nsp7, nsp8 and nsp12. Most of our understanding of coronavirus molecular biology comes from betacoronaviruses like SARS-CoV and SARS-CoV-2, the latter of which is the causative agent of COVID-19. In contrast, members of the alphacoronavirus genus are relatively understudied despite their importance in human and animal health. Here we have used cryo-electron microscopy to determine structures of the alphacoronavirus porcine epidemic diarrhea virus (PEDV) core polymerase complex bound to RNA. One structure shows an unexpected nsp8 stoichiometry despite remaining bound to RNA. Biochemical analysis shows that the N-terminal extension of one nsp8 is not required for in vitro RNA synthesis for alpha- and betacoronaviruses. Our work demonstrates the importance of studying diverse coronaviruses in revealing aspects of coronavirus replication and identifying areas of conservation to be targeted by antiviral drugs. Graphical Abstract Graphical Abstract